Involvement of large rearrangements in MSH6 and PMS2 genes in Southern Italian patients with Lynch syndrome. - Lo Monte, Attilio Ignazio; Cudia, Bianca; Liccardo, Raffaella; Izzo, Paola; Duraturo, Francesca (European Journal of Oncology and Environmental Health, 2018)
Background and aim of the work: The Lynch Syndrome (LS) is associated with germline mutations in one of the MisMatch Repair (MMR) genes. Most of germline mutations are point variants, followed by large rearrangements that account to 15-55% of all pathogenic mutations. Many study reporting the frequency of large rearrangements in the MLH1 and MSH2 genes were performed, while, little is known about the contribution of large rearrangements in other MMR genes, as PMS2 and MSH6. Therefore, in this study we investigated the involvment of large rearrangements in MSH6 and PMS2 genes in a well-characterized series of 20 LS southern Italian patients. Methods: These large rearrangements are not usually detected by methods of mutation analysis, such as denaturing high-performance liquid chromatography (DHPLC) and direct DNA sequencing, but they are detectable by a known technique as the Multiplex Ligation-Probe Dependent Amplification (MLPA) assay. Results: No large rearrangements were identified in MSH6 gene; instead, a large rearrangement was identified in PMS2 gene. A large duplication including the exons 3 and 4 of the PMS2 gene was identified in a patient who developed a rectum carcinoma at 45 years of age, an endometrial carcinoma and a vaginal cancer at the 65 years of age. Conclusion: We can affirm that the detection of large rearrangements in the MSH6 and PMS2 genes should be included in the routine testing for Lynch syndrome, especially considering the simplicity of the MLPA assay.